The art of grocery shopping on a food stamp budget: factors influencing the food choices of low-income women as they try to make ends meet - Wiig, Kristen; Smith, Chery (Public health nutrition, 2009)
Amidst a hunger-obesity paradox, the purpose of the present study was to examine the grocery shopping behaviour and food stamp usage of low-income women with children to identify factors influencing their food choices on a limited budget. Focus groups, which included questions based on Social Cognitive Theory constructs, examined food choice in the context of personal, behavioural and environmental factors. A quantitative grocery shopping activity required participants to prioritize food purchases from a 177-item list on a budget of $US 50 for a one-week period, an amount chosen based on the average household food stamp allotment in 2005. Ninety-two low-income women, with at least one child aged 9-13 years in their household, residing in the Twin Cities, Minnesota, USA. Participants' mean age was 37 years, and 76% were overweight or obese (BMI> or =25.0 kg/m2). Key findings suggest that their food choices and grocery shopping behaviour were shaped by not only individual and family preferences, but also their economic and environmental situation. Transportation and store accessibility were major determinants of shopping frequency, and they used various strategies to make their food dollars stretch (e.g. shopping based on prices, in-store specials). Generally, meat was the most important food group for purchase and consumption, according to both the qualitative and quantitative data. Efforts to improve food budgeting skills, increase nutrition knowledge, and develop meal preparation strategies involving less meat and more fruits and vegetables, could be valuable in helping low-income families nutritionally make the best use of their food dollars.